Peningkatan Hasil Belajar Ilmu Pengetahuan Alam materi Bioteknologi Pangan Melalui Penerapan Model Pembelajaran Think Pair Share di Kelas IX.7 SMP Negeri 1Cariu Kabupaten Bogor Tahun Pembelajaran 2015/2016 - Solichin (Institut Agama Islam Sahid (INAIS) Bogor, 2021)
The background of the research was that the grades of Natural Sciences (IPA) for class IX-7 SMP Negeri 1 Cariu, Bogar Regency, were not optimal. A total of 23 students (57.5%) out of 40 students scored below the Minimum Completeness Criteria (KKM) of 75. Meanwhile, 17 students (42.5%) scored above the Minimum Completeness Criteria (KKM). This research is an increase in the science learning outcomes of students on food biotechnology material through the application of the Think Pair Share cooperative learning model for class IX-7 SMP Negeri 1 Cariu, Bogar Regency, 2015/2016 Academic Year Semester 1. This research is an action research research subject. Class IX students -7 with the research location of SMP Negeri 1 Cariu for the 2015/2016 academic year. This research consists of two cycles, where in each cycle consists of planning, action, observation, evaluation and reflection. Data collection through observation and tests. The results obtained are that the implementation through the application of the Think Pair Share cooperative learning model is able to make a positive contribution to student learning activities and improve science learning outcomes for students in class IX-7 SMP Negeri 1 Cariu, Bogar Regency, 2015/2016 academic year. This is proven by an increase in student learning activities in the first cycle of 72, 73%, the second cycle of82.69 and test results. Students who in the pre-cycle have an average of 66.5 and 30% success, cycle I average is 70 and success is 52.5%, and cycle 11 is an average of 83 and success is 77, 5%.